PENGARUH MODEL PEMBELAJARAN AKTIF TIPE TEAM QUIZ TERHADAP PRESTASI BELAJAR IPA SISWA KELAS III SD NEGERI MARGOYASAN YOGYAKARTA - Retno Utaminingsih; Ganjar Alym (Universitas Sarjanawiyata Tamansiswa, 2022)
Abstract : The purpose of this study was to determine the trend of science learning achievement of third grade students of SD Negeri Margoyasan Yogyakarta using the Team Quiz type of active learning model and to determine the differences in science learning achievement of third grade students of SD Negeri Margoyasan Yogyakarta between those using the Team Quiz and expository active learning models. Data collection techniques with documentation techniques and test techniques. The results of the validity test of 30, obtained 28 items were declared valid. The results of the instrument reliability test obtained the KR-20 value of 0.923. The data analysis technique used descriptive analysis and t-test. The analysis prerequisite test used the normality test of the data distribution and the homogeneity of variance test. The results showed that the trend of science learning achievement of third grade students of SD Negeri Margoyasan Yogyakarta who used the Team Quiz type of active learning model was included in the very high category and there was a very significant difference in science learning achievement between those who used the Team Quiz type of active learning model and the expository model. Keywords: Team Quiz, Learning Achievement, Sains